International journal of web services research - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2004)
This journal is the first refereed, international publication featuring the latest research findings and industry solutions involving all aspects of Web services technology. It covers advancements, standards, and practices of Web services, as well as identifies emerging research topics and defines the future of Web services on grid computing, multimedia, and communication. IJWSR provides an open, formal publication for high quality articles developed by theoreticians, educators, developers, researchers, and practitioners for those desiring to stay abreast of challenges in Web services technology.
Also available in print.
Mode of access: World Wide Web.
"Official publication of the Information Resources Management Association."
Description based on: Vol. 1, no. 1 (Jan./Mar. 2004); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 7, no. 4 (2010).
Keywords: Web services -- Periodicals; Business grid; Business process integration and management using Web services; Communication applications using Web services; Composite Web service creation and enabling infrastructures; Dynamic invocation mechanisms for Web services; E-commerce applications using Web services; Frameworks for building Web service applications; Grid-based Web services applications; Interactive TV applications using Web services; Mathematic foundations for service oriented computing; Multimedia applications using Web services; Quality of service for Web services; Resource management for Web services; Semantic services computing; SOAP enhancements; Solution management for Web services; UDDI enhancements; Web services architecture; Web services discovery; Web services modeling; Web services performance; Web services security; Electronic books